Geotechnical Challenges in Numerical Modelling of Sarawak Fibrous Peat - Nimal, Seneviratne (International Journal of Integrated Engineering, 2014)
In Sarawak, about 13% of the total land area is covered with recent peat deposits. A complex mechanism of plant growth and peat accumulation with time has led to formation of flat topped peat domes. Dome centre consists of highly fibrous ombrogeneous peat. Topogeneous peat found in the fringes of peat domes and in interior floodplains, consists of a mixture of decomposed plant matter and fine clastic sediments. Mechanical behaviour of fibrous peat is influenced by the arrangement of fibre. The present study shows that fibrous peat as well as temperate peat conforms to a unique dry density - moisture content relationship. A preliminary study has been carried out in developing a cellular model of fibrous peat. The finite element analysis of time dependent stress strain behaviour performed using this model shows interesting results and promise of application in understanding the behaviour of fibrous peat.